Combination Effect of Three Main Constituents From Sarcandra glabra Inhibits Oxidative Stress in the Mice Following Acute Lung Injury: A Role of MAPK-NF-κB Pathway - Liu, Chun-Ping; Liu, Jian-Xing; Gu, Jiangyong; Liu, Fang; Li, Jin-Hua; Bin-Yang,; Yuan-Zheng,; Jie-Li,; Wu, Shou-hai; Wu, Qing-he; Xian-Zhang,; Li, Long-Mei; et al. (Frontiers in Pharmacology, 2021)
Caffeoylquinic acids, coumarins and dicaffeoyl derivatives are considered to be three kinds of the most abundant bioactive components in Sarcandra glabra, an anti-inflammatory herb mainly found in Southern Asia. The combined anti-inflammatory effect of three typical constituents C + R + I (chlorogenic acid + rosmarinic acid + isofraxidin) from this plant has been investigated. The result implies that targeting the MAPK-NF-κB pathway would be one of the major mechanisms involved, using LPS stimulated RAW 264.7 cells as in vitro model and LPS-induced acute lung injury in mice as in vivo model. C + R + I can significantly suppress the levels of nitric oxide (NO), pro-inflammatory cytokines, and inhibit iNOS and COX-2 expression in LPS-treated RAW264.7 macrophage cells. Western blot analysis showed that C + R + I suppressed phosphorylation of NF-κB and MAPK, including phosphorylation of p65-NF-κB, IKB, ERK, JNK and P38. Besides, C + R + I suppressed MPO protein expression, but promoted SOD and HO-1 expression, and the related targets for C, R, and I were also predicted by molecular docking. This indicated that C + R + I could alleviate oxidative stress induced by LPS, which were further verified in the in vivo model of mice with acute lung injury through the measurement of corresponding inflammatory mediators and the analysis of immunehistochemistry.